OPTIMALISASI PEMBERDAYAAN KOMUNITAS MELALUI PELATIHAN MICROSOFT OFFICE DI KAMAR DAGANG INDUSTRI JAKARTA PUSAT - Geasela, Yemima Monica; Hakim, Bhustomy; Lestari, Merryana; Ranny, Ranny; Thenata, Angelina Pramana; Kaunang, Fergie Joanda; Wijayanti, Theresia Puspa (Jurnal Pengabdian dan Kewirausahaan, 2025)
The purpose of this community service activity is to provide training for employees working at the Central Jakarta Chamber of Commerce and Industry (KADIN) (PKM partner) on optimizing Microsoft Office to support office work. This topic is deemed essential for every employee. The employees of Central Jakarta KADIN are aged around 35–50 years, representing Indonesia's Baby Boombers workforce generation, who are relatively less familiar with the use of Microsoft Office. However, they exhibit remarkable enthusiasm to understand and learn Microsoft Office in greater depth. Central Jakarta KADIN serves as a platkuisioner for entrepreneurs to foster professional development, channel aspirations, and advocate for business interests in supporting national development. The PKM activity was conducted face-to-face from September 2 to October 9, 2024, with a total of 40 participants attending all sessions. Participants actively engaged in hands-on practice sessions on using Microsoft Office. The method used was demonstration, where instructors directly showed the steps and ways to use the menus and toolbars in Microsoft Office. Participants rated the presented topic as highly relevant and beneficial, with a umpan balik score of 3.89 out of 4. In the future, the partner hopes for the continuation of similar activities, focusing on more advanced aspects of Microsoft Office or other topics that can further support their work efficiency and productivity.